Optimasi Celah Geometrik Ripple Mill dalam Menyeimbangkan Efisiensi Pemecahan Biji dan Integritas Inti Sawit di PKS Bah Jambi - Maren sius girsang; Jhon Supriadi Purba (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
In the palm oil extraction process, the efficiency of the ripple mill is critical to maximizingkernel recovery while minimizing losses. This study aims to evaluate the impact of theclearance between the rotor bar and the ripple plate on the cracking efficiency and kernelquality at the PKS Bah Jambi palm oil mill. Experimental tests were conducted under normalindustrial operating conditions by varying the rotor bar–ripple plate distance at four levels: 8mm, 9 mm, 10 mm, and 11 mm. A 1000-gram sample of the cracked mixture was collected foreach setting and manually separated into five fractions: whole nuts, cracked nuts, wholekernels, broken kernels, and shells to calculate the cracking efficiency and mass percentages.The results demonstrate that the geometric clearance significantly controls the quality andefficiency of nut cracking. Increasing the clearance from 8 mm to 11 mm led to a significantdecrease in cracking efficiency from 98.05% to 94.57%, falling below the mill's minimumstandard of 97%. While wider clearances offered better protection for the kernels (reducingbroken kernels), they resulted in higher kernel losses due to the increased volume of uncrackedand partially cracked nuts.To maintain optimal performance, the mill management shouldstandardize the rotor-plate distance at 8–9 mm, which ensures an efficiency rate above 97%while maintaining acceptable kernel breakage levels. It is recommended that this setting beintegrated into the Standard Operating Procedures (SOP), supported by routine wearinspections and the reactivation of nut grading drums to ensure feedstock uniformity and stablemill performance.Keywords: Ripple Mill, Cracking Efficiency, Palm Oil Mill.